2022
DOI: 10.24221/jeap.7.3.2022.4931.135-149
|View full text |Cite
|
Sign up to set email alerts
|

Edge effect on vascular epiphytes in a subtropical Atlantic Forest fragment

Abstract: Epiphytes are efficient indicators of environmental quality. The Atlantic Forest is a hotspot for epiphyte richness; however, it is experiencing one of the highest rates of degradation, exposing epiphytes to edge effects. This study aimed to evaluate the floristic composition and richness of vascular epiphytes and their relationship with phorophyte features and microenvironmental variables at the edge and in the interior of a subtropical Atlantic Forest fragment in Brazil. Twenty-five trees were analyzed, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…2023 it is isolated, it is under the direct influence of the edge effect in all its cardinal limits. Previous studies in this location revealed biological elements, such as high epiphyte diversity, which classify this area as a secondary forest with advanced ecological succession (Endres Júnior et al 2015;Lippert et al 2022;Quevedo et al 2014;Brasil 1994).…”
Section: Study Area and Climatementioning
confidence: 81%
“…2023 it is isolated, it is under the direct influence of the edge effect in all its cardinal limits. Previous studies in this location revealed biological elements, such as high epiphyte diversity, which classify this area as a secondary forest with advanced ecological succession (Endres Júnior et al 2015;Lippert et al 2022;Quevedo et al 2014;Brasil 1994).…”
Section: Study Area and Climatementioning
confidence: 81%